2018
DOI: 10.1016/j.asr.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Advanced illumination modeling for data analysis and calibration. Application to the Moon

Abstract: We present a new illumination modeling tool, called IllumNG, developed at NASA Goddard Space Flight Center (GSFC). We describe its capabilities to enhance the analysis and calibration of science data collected by planetary missions. We highlight these with examples making use of lunar data, particularly the topographic and radiometric measurements collected by the Lunar Orbiter Laser Altimeter (LOLA) instrument, with applications to radiometric measurements from other LRO instruments as well. The unique featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…After the high-resolution DEMs were produced for all eight craters, solar illumination models (e.g., Figure 3(b) ) were made at 125 m pixel −1 following the methodology of Mazarico et al (2011 , 2018 ) for lunar craters. These solar illumination models employed a double-precision ray-tracing method to determine the fraction of a Mercury solar day (176 Earth days) in which Mercury’s polar surface is directly illuminated by any portion of the Sun ( Mazarico et al 2011 , 2018 ). These illumination models treated the Sun as a disk, not a point source, due to the large areal coverage of the Sun in Mercury’s sky ( Mazarico et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the high-resolution DEMs were produced for all eight craters, solar illumination models (e.g., Figure 3(b) ) were made at 125 m pixel −1 following the methodology of Mazarico et al (2011 , 2018 ) for lunar craters. These solar illumination models employed a double-precision ray-tracing method to determine the fraction of a Mercury solar day (176 Earth days) in which Mercury’s polar surface is directly illuminated by any portion of the Sun ( Mazarico et al 2011 , 2018 ). These illumination models treated the Sun as a disk, not a point source, due to the large areal coverage of the Sun in Mercury’s sky ( Mazarico et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…These solar illumination models employed a double-precision ray-tracing method to determine the fraction of a Mercury solar day (176 Earth days) in which Mercury’s polar surface is directly illuminated by any portion of the Sun ( Mazarico et al 2011 , 2018 ). These illumination models treated the Sun as a disk, not a point source, due to the large areal coverage of the Sun in Mercury’s sky ( Mazarico et al 2018 ). We found that ~100 elements are sufficient, after evaluating several simulations with up to several thousand elements to discretize the solar disk.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For other processing tasks, such as producing filter-specific albedo maps of the surface and calculating the corresponding albedo distribution , the absolute radiometric uncertainty is paramount. To assess the absolute radiometric accuracy, we perform an independent calibration with an illumination model of the Moon from NASA Goddard Space Flight Center (Mazarico et al 2018), based on SELENE (Kaguya) Multiband Imager (MI) global mosaics (Lemelin et al 2019;Ohtake et al 2013). We simulate images of identical observation geometry, as shown in Fig.…”
Section: Radiometrymentioning
confidence: 99%